Further Results on Lacunary Difference Sequences of Complex Uncertain Variables in 2-Normed Spaces - Kişi, Ömer; Güler, Erhan (International Conference on Applied Engineering and Natural Sciences, 2023)
A novel approach combining the difference operator on sequence spaces and uncertainty theory has been utilized to establish a fresh class of lacunary convergent difference sequences involving complex uncertain variables in 2-normed spaces. This newly introduced class demonstrates remarkable properties related to lacunary convergence. Additionally, the sequence spaces defined in this context have been thoroughly explored, revealing interesting topological characteristics and valuable insights into inclusion relations. This study offers a rejuvenated perspective on lacunary convergence and its associated concepts through the integration of difference operators and uncertainty theory.